Ujian Nasional, Dulu, Kini dan yang Akan Datang: Tinjauan Normatif - Muntholi’ah Muntholi’ah (Nadwa: Jurnal Pendidikan Islam, 2013)
The policy of the National Examination (UN) continues to get criticism from education experts, practitioners, as well as various elements of society. With the  problems happen in the implementation of National Examination, it can be af-firmed that the impacts of its implementation are more harmful than the objec-tives to be achieved. Considering the imbalances and disadvantages of the Na-tional Examination implementation, the government through the Ministry of Education should have to be more thoughtful and immediately review the policy  comprehensively. Thus, the purpose of education should be tailored to the interests of Indonesia, which is stated and defined in the the National Education Law No. 20/ 2003 on National Education System Chapter II, Article 3. AbstrakKebijakan Ujian Nasional (UN) terus menuai kritik dari para pakar dan praktisi pendidikan serta berbagai kalangan  masyarakat. Melihat banyaknya permasalahan dan carut-marut dalam pelaksanaan Ujian Nasional dapat ditegaskan bahwa dampak dari penyelenggaraan UN lebih banyak mudaratnya dari pada tujuan yang ingin dicapai. Menilik berbagai ketimpangan dan kemudaratan yang ditim bulkan akibat pelaksanaan UN, maka seyogianya pemerintah melalui Kemendiknas harus bersikap lebih bijaksana dan segera mengkaji ulang kebijakan UN secara komprehensif. Dengan demikian maka tujuan pendidikan yang hendak dicapaipun disesuaikan dengan kepentingan bangsa Indonesia, yang sekarang initujuan pendidikan tersebut dirumuskan dalam Undang-Undang Nomor 20 tahun 2003 tentang Sistem Pendidikan Nasional (UU sisdiknas) BAB II pasal 3.